Brooding sea anemones (Cnidaria: Anthozoa: Actiniaria): paragons of diversity in mode, morphology, and maternity. Issue 1 (14th February 2017) - Larson, Paul
Abstract: Brooding has been reported in at least 57 species of sea anemone. More than three quarters (44/57) of the species that are known to brood have been described since the last comprehensive treatment of brooding in this lineage. Different authors focusing on different taxonomic groups within sea anemones over the last 115 years have collectively produced an imprecise and inconsistent set of terminology with respect to brooding in general and to the variety of conditions of brooding in particular. In this review, I characterize brooding as a behavior in which offspring are retained by the adult to at least the juvenile stage, in contrast with the more common release of eggs, embryos, or larvae. Brooding occurs in two primary modes, internal and external, in which offspring may be produced via sexual or asexual means. I categorize structures associated with external brooding in three types: pits, chambers, and grooves. Early inferences that external brooding has a primarily bipolar distribution continue to be supported with current data, but it is doubtful that small size and simultaneous hermaphroditism are correlated with brooding in sea anemones. Finally, I identify open questions about brooding in sea anemones and suggest future lines of research that will broaden our understanding of this phenomenon.